Decadal changes in ozone in the lower boundary layer over Beijing, China. (15th April 2022) - Liu, Yusi; Tang, Guiqian; Liu, Baoxian; Zhang, Xiao; Li, Qihua; Hu, Qihou; Wang, Yu; Yu, Miao; Sun, Yang; Ji, Dongsheng; Wang, Yinghong; Wang, Yuesi
Abstract: Since NOx has decreased significantly, ozone formation sensitivity in urban areas has gradually shifted from VOC-limited to NOx-limited. Ozone is usually formed at high altitudes. However, due to a lack of vertical gradient observation data support, the evidence of high-altitude sensitivity change is still not conclusive. To confirm this issue, ozone and NOx were observed at three heights (8 m, 160 m, and 280 m) from a 325 m tower in Beijing from 2019 to 2020. Combined with the NO2 and HCHO column concentrations, the ozone formation sensitivity transition was determined, and it was proposed that NOx control could effectively deal with high ozone concentrations. By comparing the observations from 2009 to 2010, near-surface NOx and ozone concentrations were found to have changed. A large decrease in NOx (−20 ppbv) and increase in ozone (19 ppbv) indicated that the weakening of the NO titration effect was the main cause of the increase. To remove the influence of the titration effect, the change in Ox (Ox = O3 +NO2 ) was analyzed and found to have increased by 6 ppbv. Local formation was not the main reason for Ox growth. After strict emission standards, the proportion of primary NO2 and southward short-distance transport increased, which were two key reasons for the Ox increase. In addition, the boundary layer height increased by 208 m, and the surface relative humidity decreased by 6%. Meteorological conditions have become more conducive to ozone formation. This study shows that NOx emission reduction is conducive to controlling high-level ozone pollution. With the in-depth development of NOx emission reduction, the near-surface ozone will also significantly decrease. This study also highlights the importance of strict controls on diesel vehicles and motor vehicle numbers. Highlights: Meteorological conditions have become more favorable for ozone formation. Primary NO2 and southward short-distance transport increased. Continuous NOx reduction can control ozone pollution. VOCs should be controlled throughout the year, and NOx in summer.